Supporting system development by novice software engineers using a tutor-based software visualization (TubVis) approach - Sulaiman, Shahida; Abdul Rashid, Nur Aini; Abdullah, Rosni; Sulaiman, Sarina (2008)
Most computer-aided software engineering (CASE) products provide visualization utility to view software artefacts developed. Nevertheless, existing methods or approaches in such tools are limited to generating the views or component dependencies that is focusing on twhat' the output ofreverse engineering process. The online help provided by the tools only indicate thow' to use the tools to generate the views. Since existing tools mostly target for experienced software engineers, they tend to overlook the need ofexplaining twhy' the output is recommended or not with regard to software engineering principles. Hence we propose tutor-based software visualization (Tub Vis) approach in So Vis tool that analyses software artefacts pertaining to software engineering best practices inputted by the experts and generate a set of recommendations regarding the design and coding for a novices. We anticipate TubVis can improve the quality of software design and program comprehension by combining practical and theoretical aspects of software engineering education in a software visualization tool.